The Effectiveness of Multimedia Science Learning to Improve Environmental Care Character in Junior High School Students: - Lanto Mohamad Kamil Amali; Nova Elysia Ntobuo; Ratha Doung; Moh. Hidayat Koniyo; Rithin Uloli; Meylan Demulawa; Lato Chairinnisa Amali (Universitas Syiah Kuala, 2026)
The importance of environmental awareness is demonstrated by the government through environmental care initiatives and by making environmental care a key element of nationalistic values. Therefore, fostering an environmental care character is essential to be cultivated from an early age and developed effectively. Character education in educational settings can be implemented through the use of multimedia learning that integrates character education. Several studies indicate that the use of ICT (information and communication technology) multimedia can enhance students' character. However, access to ICT multimedia for strengthening environmental care character remains difficult to obtain. Based on this, the purpose of this research is to develop an ICT-based Science Learning Multimedia (that is valid, practical, and effective) to enhance the environmental care character of junior high school students as an effort to improve the quality of the environment. The research method used is a development method, adopting the four-D model, which consists of the following stages: 1) Definition: identifying and formulating learning requirements, determining objectives, and addressing issues in existing media or teaching tools; 2) Design: designing the multimedia; 3) Development: conducting limited and extensive trials; and 4) Dissemination: distributing the product. This research resulted in a multimedia learning application that is considered valid based on expert assessments, and practical and effective in improving the environmental care character of junior high school students. The enhanced environmental care character includes increased student involvement in maintaining cleanliness, energy conservation, waste sorting and processing, as well as participation in environmental preservation activities